Metal Film-Based Flexible Sensor for Omnidirectional Airflow Measurement - Che Abdullah, Sukarnur; Azmi, Mohamad Hadis; Mat Jusoh, Mohammad Azzeim; Amari, Mohamad Dzulhelmy (International Journal of Integrated Engineering, 2025)
The previous study on airflow sensors were fabricated using a flap device printed using polylactic acid (PLA) plastic, which had high stiffness, preventing the sensor from bending and returning to its original shape. The used aluminium (Al) strips exhibited relatively higher resistance values compared to copper (Cu), resulting in inconsistent resistance readings at various angles of bending measurement. This paper presents a new development of an enhanced metal film-based flexible sensor for application on omnidirectional 360-degree airflow measurement. The sensor was fabricated using copper film and velostat, a material made of polymeric foil (polyolefins) infused with carbon black to make it electrically conductive. The flapping device was modelled in SolidWorks (3D CAD) and printed using TPE 83A (Thermoplastic Elastomer) filament on a 3D printing machine. An Arduino Mega was used as a controller, data collector, and for evaluating the results. The copper film and TPE 83A material demonstrated significant potential in developing a new flexible sensor for achieving high-accuracy airflow measurement in omnidirectional.